Association between maternal circulating 25 hydroxyvitamin D concentration and placental volume in the first trimester. (17th December 2017) - Yayla Abide, Çiğdem; Kurek Eken, Meryem; Turan, Işıl; Özkaya, Enis; Pekin, Oya; Karateke, Ateş
Abstract: Objectives: We aimed to assess placental volume and placental mean gray value in vitamin D deficiency and healthy placentas in the first trimester of pregnancy using three-dimensional (3D) ultrasonography (USG) and Virtual Organ Computer-aided Analysis (VOCAL). Methods: This prospective cross sectional study comprised 274 patients, divided into two groups according to the presence or absence of vitamin D deficiency (<20 ng/ml deficient, n = 153, >20 ng/ml not deficient, n = 121) in the first trimester of pregnancy. Placental volume and placental volumetric mean gray values were evaluated. Placental volume (cm 3 ) was analyzed using the VOCAL imaging program and a 3D histogram was used to calculate the volumetric mean gray value (%). Results: Placental volume was significantly less in the vitamin D deficiency group ( p = 0.017) Volumetric mean gray value of the placenta was significantly higher in the vitamin D deficiency group ( p = 0.003). Maternal serum PAPP-A (MoM) and f-β Hcg (MoM) were significantly lower in the vitamin D deficiency group ( p = 0.008, p = 0.003, respectively). In linear regression analyses, serum vitamin D concentration was significantly associated with the plasental volume ( β = 0.16; p = 0.01). Conclusion: Placental configuration and development were associated with vitamin D even in the first trimester of pregnancy. To ensure healthy pregnancy outcomes, vitamin D screening applied in the early stages of pregnancy or even before pregnancy.